EFFECTS OF GLYPHOSATE POTASSIUM 660 G L⁻¹ ON TRANSGENIC AND CONVENTIONAL CORN VARIETIES - Denny Kurniadie; Uum Umiyati; Dedi Widayat (SEAMEO BIOTROP, 2019)
The transgenic corn variety, NK 603, which contains a gene called CP4 EPSPS (5-enolpyruvyl shikimate-3-phosphate synthase) which makes the corn plants tolerant to the glyphosate herbicide, on the other hand conventional corn varieties are sensitive to glyphosate. It was required to test the chlorosis and burn-down effect both in transgenic and conventional corn varieties due to glyphosate. The experiment was conducted to quantify the burn-down effects and chlorosis due to the application of herbicide glyphosate potassium 660 g L⁻¹ on two varieties of corn at the Agriculture Faculty Research Station of Padjadjaran University, West Java, Indonesia, from December 2015 to April 2016. The experiment was arranged in randomized block design with 20 treatments and each treatment replicated twice. At 15 days and 20 days after planting, five transgenic corn varieties (C 7 RR, 979 RR, 77 RR, 85 RR and 95 RR) and five conventional corn varieties (C 7, 979, 77, 85 and 95) were applied with herbicide glyphosate potassium 660 g L⁻¹ at a dose of 2 L ha⁻¹. The results showed that the herbicide was effective to control the weed in both transgenic and conventional corn varieties. The transgenic corn variety exhibited smaller percentages of chlorosis (0–20%) and no burn-down effect was observed following applications of glyphosate potassium 660 g L⁻¹. On the other hand, chlorosis and burn-down effects were found on all conventional corn varieties. The yield of transgenic corn varieties was higher than those of the conventional corn varieties.